Flexural properties of kenaf fibre hybrid and non-hybrid composite materials - Azmi, A. M. R.; Sultan, M. T. H.; Shah, A.U.M.; Jawaid, M.; Nor, A. F. M.; Ismail, K. I. (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Natural fibre are well known for its properties where it has low density and it is also better in form of cost efficiency compared to synthetic fibre. There are not too much difference between specific properties of natural fibre and synthetic fibre although the natural fibre strength is significantly lower than synthetic fibre. This study discusses the flexural properties of a hybrid composite made from both natural fibre and synthetic fibre. In this research, kenaf fibre – non-treated and treated with NaOH solution – as well as x-ray film – non-treated and surface treated with consistent holes were chosen to investigate its flexural properties. The number of layers in this study is maintain throughout the research, which are seven layers of kenaf – treated and untreated – as well as alternating layers between kenaf fibre and x-ray films – also treated and untreated. The specimen were prepared using the normal hand lay-up process and it was tested by the three-point bending method using Instron 4204 at a speed of 15mm/min. Even though the test showed expected problems such as interfacial bonding issues, there are improvements due to treatment and the hybridization. The specimen showed results of flexural modulus of up to 8.83GPa for treated fully kenaf configuration and 3.36GPa for alternative configuration with treated kenaf. The higher flexural modulus is suitable for applications which desire a more rigid structure like a spall linear or car bumper, while the specimen with the lower flexural modulus is suitable for a more flexible structure like body armour.